Beyond the knowledge production function: the role of R&D in a multi-faceted innovative process - Alessandra Catozzella; Marco Vivarelli (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
The purpose of this paper is to test the possible catalysing role of in-house R&D in fostering the complementarity of innovative inputs on a sample of 3045 manufacturing firms drawn from the third Italian Community Innovation Survey (1998-2000). The interactions between four different sources of innovation – internal and external R&D, embodied and disembodied technological acquisitions – have been simultaneously explo-red through the two (direct and indirect) testing frameworks for complementarity. Results from both the approaches show that the innovative process is a pheno-menon combining within itself both complementarity and substitutability relationships, de-pending both on the typology of the targeted innovation output and on the particular com-bination of innovative inputs we focus on. In particular, it is in-house R&D that seems to create the precondition allowing firms to enjoy complementarity effects. Indeed, the possi-bility of exploiting synergies between different innovative inputs turns out to be subordi-nated to having undertaken a minimum amount of internal R&D. The implication of this result is that a role for in-house R&D emerges, beyond its di-rect effect in generating an innovative output: even if internal research is not a necessary precondition for a firm to be innovative, it should still be carried out because of its im-portant role in the generation of synergies that amplify the impacts of the other innovative inputs it interacts with.
Keywords: O31; 330; R&D; innovation; complementarity; supermodularity; substitutability; Industrielle Forschung; Innovation; Wissen; Produktionsfunktion; Italien